La energía como núcleo en el diseño curricular de la física - Pérez-Landazábal, M. C.; Favieres, A.; Manrique del Campo, Mª J.; Varela, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
A research' study on an approach to Physics teaching, at a basic level, centered on energy is presented. This study, framed on the Constructivist theory of learning, has led to the design of curricula materials and their implementation and evaluation in secondary classrooms. An initial exploration of the prior beliefs of pupils about energy constituted the base of this curricula materials.